Physical oceanography (CTD) during Meteor cruise M150 - Manfred Kaufmann; Barbara Springer; Gerd Krahmann; Kai Horst George (PANGAEA, 2020)
Salinity and Oxygen were not calibrated beyond the manufacturer extquotesingles calibration coefficients. Compared to climatological values (WOA18) salinity appears to be 0.05 PSU too low. Both CTD sensors and the two TSG sensors do however agree. Oxygen values are in the range of the climatological values, possibly 5 umol/kg too low. Some deep profiles show consistently low oxygen values that is not represented in the climatology. Use this data with caution.